CD109 is a novel marker for squamous cell/adenosquamous carcinomas of the gallbladder - Dong, Fengyun (Diagn Pathol, 2015)
Gallbladder cancer is the most common biliary tract malignancy with the worst overall prognosis. CD109 is a co-receptor of TGF-β1 and suppresses TGF-β signaling. In this study, CD109 protein expression in three subtypes of gallbladder cancer was examined by immunohistochemistry on human tissue samples and tissue microarrays. We found that CD109 is specifically expressed in malignant squamous cells in squamous cell carcinomas (86.7 %) and adenosquamous carcinomas (91.7 %), but not in adenocarcinomas or normal gallbladder tissues. Thus, CD109 may be a potential pathology marker for gallbladder squamous cell/adenosquamous carcinomas.